TAJIK-AFGHAN INTERRELATIONS TODAY AND THEIR FUTURE PROSPECTS - ISKANDAROV, Kosimsho (CENTRAL ASIA AND THE CAUCASUS, 2008)
The Republic of Tajikistan and the Islamic Republic of Afghanistan1 have all the prerequisites for developing good-neighborly relations: a long common border stretching 1,344 km,a common historical past, common cultural values, traditions, and customs, a common religion, and a common language. According to different estimates, Tajiks comprise between 25% and 34% of the population of Afghanistan, where more than 40 nationalities live who speak 30 languages. More than half of the population speak Dari (as the language of the Tajiks of Afghanistan is called), which is one of the two official state languages of this republic. Until 1936, the language of the Tajiks of Afghanistan was the only state tongue, as well as the means of international communication. The collapse of the U.S.S.R. and Tajikistan’s acquirement of state sovereignty coincided timewise with the mojaheds’ advent to power in Afghanistan in April 1992. Recognizing the Islamic State of Afghanistan (ISA) from the very first days of its existence, the Republic of Tajikistan declared its willingness to establish good-neighborly relations between the two sovereign states, which was demonstrated during the first official visit of a high-ranking Tajik government delegation headed by acting Chairman of the Tajik Supreme Soviet A. Iskandarov to Kabul in July 1992. This fact is noteworthy since it was the first visit by a government delegation of the already independent Tajik state, and the Afghan state was also headed by Tajiks. The country’s president was Burhanuddin Rabbani, the prime minister was a member of the Islamic Party of Afghanistan, Tajik Abdul Sabur Farid, and the minister of defense was Ahmad Shah Masud.